Efektifitas Penilaian Portofolio Pada Mata Pelajaran SBDP Di Sekolah Dasar - ., Ryzca Siti Qomariyah; ., Nur Afrika Lita Dewi; ., Isma Aini Nafis; ., Lely Nur Fitria (CV. ITTC INDONESIA, 2022)
This study aims to determine the degree of equity in the use of the portfolio assessment approach in elementary schools. This observation was carried out in October 2022 at SDN PABEAN. The research method that we use in this observation is a qualitative method. Qualitative research aims to capture and understand the meaning of a context in the current conditions and not make it up, in which we extract information from the material we choose, namely portfolio assessment and re-decipher the information we have obtained from this observation. In this portfolio assessment there are things that need to be given special attention, especially on the cognitive, affective, and psychomotor aspects. So by paying attention to these three things, the teacher can improve the quality of each student's portfolio assessment so that there is continuity in every aspect of project-based and non-project-based assessments.